Optimization of surgical treatment of epidermoid brain tumors. - Sirko, A. G.; Romanukha, D. N. (Medicni Perspektivi, 2015)
Despite the relatively rare occurrence of epidermoid brain tumors (EBT), high rates of postoperative mortality and a high incidence of tumor recurrence are marked in the operated patients. The purpose of research is to improve treatment results of patients with EBT by determining optimal treatment tactic. A retrospective research of 17 patients with verified EBT was carried out and literary sources on various problems of their surgical treatment were analyzed. By localization EBT were devided as following: subtentorial localization was observed in 8 (47%) patients, supratentorial – in 7 (41%). Two patients (12%) had suprasubtentorial localisation of EBT. Intra- and postoperative complications were observed in 3 (18%) of cases; of patients 18% (3 patients) were discharged with deterioration of neurological status. The main purpose in EBT removing is total tumor removal in conditions of preventing iatrogenic injury of vessels, nerves and functionally important brain areas. Radical removal of cholesteatomas using microsurgical techniques with relatively low complication level provides a long disease-free period and a high quality of life of operated patients.